The Peacock Emporium - Moyes, Jojo 1969- ([New York, New York] : Penguin Books, 2019)
"Athene Forster embraced the Sixties like few others. Nicknamed the Last Deb, she was spoiled, beautiful, and out of control. And within two years of her marriage, the rumors had begun again. Thirty-five years on, Suzanna Peacock finds refuge from her mothers shameful legacy in her shop, the Peacock Emporium. Within its magical walls she discovers not just friendship, and an escape from her troubled marriage, but the first real passion of her life. But the specter of her mother still haunts Suzanna, setting in place a series of dramatic events. Only by confronting the past will she finally be able to face the future"--
"First published in Great Britain by Hodder & Stoughton, an imprint of Hachette UK, 2004"--Copyright page.
"A novel"--Cover.
Keywords: Mothers and daughters; Fiction; Community life -- England; Fiction; Specialty stores; Fiction; Coffee shops; Fiction; Families; Fiction; Families; Fiction; England; Fiction; Romance fiction; Domestic fiction